Healthy Food Counseling with Media Posters and Fun Cooking at The Pondok Harapan Surabaya Orphanage - Latifahtur Rahmah; Novi Indah Permata Sari; Ryan Yeremia Iskandar; Jefanny Vercell; Nadhira Amalia Putri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
An orphanage is not only a place to receive orphans or children abandoned by their parents, but also an institution to educate children, one of which is education on healthy food. The method used in fun education is posters with interesting pictures and games that use fun interactions for children, namely fun cooking. In the implementation stage, the educational theme given on the first day was education on healthy and unhealthy foods, while the theme on the second day was the nutritional content of healthy foods. In the healthy food fun cooking training on the first day, namely making sushi and the second day, namely mille crepes. The results of the guess the picture evaluation showed that 100% of the children in the orphanage were able to answer all the questions correctly. Finally, closing is closed by eating together. The food given to the children is a healthy meal made by international OTTIMO students, this is done to provide real examples of healthy food for the younger orphanages.